Self-regulation and communication skills in children with moderate learning difficulties - Lamb, Susannah J. (2002)
Self-regulation is increasingly considered to play an important part in several aspects of learning. It has also been claimed to be a strong candidate in explaining many of the difficulties faced by children with learning difficulties. Difficulties in monitoring one's own comprehension and controlling one's own cognitive processes, for example, is likely to affect progress on many school tasks. At the same time, the language and communication difficulties frequently faced by children with learning difficulties can also be explained by reference to poor self-regulatory skills.